Administrative Reform in Indonesia: How Far is The Citizens Online Complaints-Handling System (LAPOR!) About to Reach The Open Government Agenda? - Maryam, Dilani; Hadi, Adi Nurul; Palupijati, Ria Putri (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2018)
Indonesia is one of the most prominent countries that have a strong interest in implementing open government agendas. In 2011, the Indonesian government along with seven other country leaders took the initiative to form a global network movement called Open Government Partnership (OGP) as a platform in making their governments more open, accountable, and responsive to citizens. To connect the international agendas with national bureaucratic reforms agenda, the Indonesian government also establish the movement called Open Government Indonesia (OGI). Under the national public complaints management system, LAPOR! was established as the flagship of the open government movement to encourage a